2010
DOI: 10.1016/j.chembiol.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Complete Biosynthesis of Erythromycin A and Designed Analogs Using E. coli as a Heterologous Host

Abstract: Erythromycin A is a potent antibiotic long-recognized as a therapeutic option for bacterial infections. The soil-dwelling bacterium Saccharopolyspora erythraea natively produces erythromycin A from a 55 kb gene cluster composed of three large polyketide synthase genes (each ~10 kb) and 17 additional genes responsible for deoxysugar biosynthesis, macrolide tailoring, and resistance. In this study, the erythromycin A gene cluster was systematically transferred from S. erythraea to E. coli for reconstituted biosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 37 publications
2
98
0
1
Order By: Relevance
“…[228] Further trials were put to test by replacing a specific domain or module with its counterpart from different organisms (Figure 14a). [207] This hybrid PKS could successfully adopt the reactions from different organisms into the host PKS machinery. In 2001, Rowe et al succeeded in producing a new polyketide by inserting rapamycin module 2 between DEBS module 1 and module 2 (Figure 14b).…”
Section: Repurposing Pks For Novel Polyketide Biosynthesismentioning
confidence: 99%
See 3 more Smart Citations
“…[228] Further trials were put to test by replacing a specific domain or module with its counterpart from different organisms (Figure 14a). [207] This hybrid PKS could successfully adopt the reactions from different organisms into the host PKS machinery. In 2001, Rowe et al succeeded in producing a new polyketide by inserting rapamycin module 2 between DEBS module 1 and module 2 (Figure 14b).…”
Section: Repurposing Pks For Novel Polyketide Biosynthesismentioning
confidence: 99%
“…In the case of erythromycin A production, Zhang et al observed that erythromycin B kept accumulating, thus concluded that eryK-encoding an enzyme converting erythromycin B into erythromycin A-needed to be overexpressed. [207] It…”
Section: Reinforcing Enzymatic Bottlenecksmentioning
confidence: 99%
See 2 more Smart Citations
“…Actinomycetes are an important resource for the production of secondary metabolites with various bioactivities including antibiotics, antifungal, anticancer and immunomodulation. SysME has been increasingly employed to allow more efficient design, control and optimization of these secondary metabolites (Weber et al ., 2015), as showcased for erythromycin (Pfeifer et al ., 2001; Zhang et al ., 2010). These achievements have been made possible through large gene cluster cloning (Yuan et al ., 2016), coordinated gene expression optimization (Na et al ., 2013) and genome editing techniques (Wang et al ., 2012) among many other SysME tools developed.…”
mentioning
confidence: 99%